Types of cooking stove and risk of Acute Lower Respiratory Infection among under-five children: a cross sectional study in Rasuwa, a Himalayan district of Nepal - Sharma, Sudesh Raj; Bhandari, Nitin Nischal; Bhandari, Ram; Wagle, Kusum; Adhikari, Mukesh (Health Prospect, 2015)
Background: In Nepal, about 75% people rely on wood and other biomass fuels for cooking. The majority of Nepali families cook on a traditional stove, an open fire in the kitchen resulting in indoor air pollution, one of the key risk factors for Acute Lower Respiratory Infection (ALRI) among under-five children.The study aimed at exploring the association of indoor air pollution due to use of traditional cooking stoves with ALRI among under-five children in Rasuwa, a Himalayan district of Nepal. Methods: A cross-sectional survey was conducted in Rasuwa district from October to November 2011. The mothers with under-five children who lived in household using biomass fuels were interviewed. The total sample size of 210, calculated on the basis of Proportion to Population Size, was selected by using cluster sampling method. Children who suffered from common cold and fast breathing/higher respiratory rate were defined as having ALRI. Logistic regression was used to find out association of types of cooking stove and other factors with ALRI among the children. Results: Only about 30% of the households used improved stoves for cooking. Nearly one-third (31.4%) of the children under five years of age who lived in household using biomass fuels suffered from ALRI. After adjusting for the factors like mother’s group status, ethnic group, age of children, mother’s group membership status and father’s occupation, use of traditional/open type of cooking stove was found to be highly associated with ALRI [aOR:2.30; 95%CI (1.03-5.10)] among children. Conclusion: Exposure to smoke from a traditional stove is one of the factors leading to ALRI among children. The ALRI could be substantially reduced if these stoves be replaced by improved ones in rural areas of Nepal.